An authentic assessment model to assess kindergarten students' character - Umi Faizah; Darmiyati Zuchdi; Yasir Alsamiri (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2019)
The aim of character development is essential to know, especially for kindergarten pupils. It might help teachers in developing students and offering helps and services. Thus, an assessment model is needed to identify children's character development easily and accurately. This study aims to (1) develop an assessment model for evaluating kindergarten pupils’ character which is considered valid, reliable, and fulfill the criteria of goodness of fit statistic, and (2) know the characteristics of an authentic assessment model instrument to assess the achievements of early childhood characters in kindergarten. This research used Plomp’s Research and Development Model. Data were collected using a questionnaire, documentation, interview, observation, and Focus Group Discussion. The validation was proven by the expert judgment with the Aiken’s V formula and the reliability was estimated with Cronbach’s Alpha. The validation construct and reliability were examined using Exploratory Factor Analysis, followed by Confirmatory Factor Analysis to ensure the result. Furthermore, the results of this research show that (1) the assessment model developed is ASOKA. This model is considered valid and reliable as it meets the criteria of goodness and fits the statistic; (2) the characteristics of an authentic assessment model instrument to assess the achievements of early childhood characters in kindergarten are: (a) with the index of Aiken's V analysis results of 0.901, the content validity is considered high; (b) the instrument construct validity has fulfilled the criteria of goodness of fit statistic; (c) as seen from Alpha Cronbach value coefficient 0.914, its instrument reliability is considered good enough.